2018
DOI: 10.1063/1.5005582
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of collisional sheath in electronegative plasma with q-nonextensive electron distribution

Abstract: Electronegative plasma sheath is addressed in a collisional unmagnetized plasma consisting of q-nonextensive electrons, Boltzmann distributed negative ions and cold fluid positive ions. Considering the positive ion-neutral collisions and ignoring the effects of ionization and collisions between negative species and positive ions (neutrals), a modified Bohm sheath criterion and hence floating potential are derived by using multifluid model. Using the modified Bohm sheath criterion, the sheath characteristics su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 37 publications
5
38
0
1
Order By: Relevance
“…Finally, for our plasma model, the hot q ‐nonextensive electron density is expressed as, nh=nnormalh01+q1italiceϕTnormalhq+12q1, …”
Section: Theoretical Model and Basic Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, for our plasma model, the hot q ‐nonextensive electron density is expressed as, nh=nnormalh01+q1italiceϕTnormalhq+12q1, …”
Section: Theoretical Model and Basic Equationsmentioning
confidence: 99%
“…Finally, for our plasma model, the hot q-nonextensive electron density is expressed as, [20,34,55] n h = n h0…”
Section: Theoretical Model and Basic Equationsmentioning
confidence: 99%
“…For example, Hatami studied the sheath formation criterion in a collisional plasma consisting of non‐extensively distributed electrons and thermal ions, and discussed the effect of non‐extensive electrons on the behaviour of the density distribution of charged particles. Furthermore, the sheath in the presence of two‐temperature q ‐non‐extensive electrons in the electronegative plasma was investigated recently and it's shown that the presence of non‐extensive electron strongly modifies the sheath structure. In their model, the investigations are limited to the plasma sheath without dust particles.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of plasma sheath is of great importance due to its application in different areas such as plasma probes, low-temperature plasma-aided material processing, as well as fusion research. [21][22][23][24][25][26][27] For example, Driouch and Chatei investigated a magnetized dusty plasma sheath in the presence of a q-non-extensive distribution of electrons. [4][5][6][7][8] Since the forces acting on the dust particles and charging processes are important in characterization of the plasma sheath, numerous research studies investigated these effects and it was found that the presence of dust nanoparticles modifies the structure of the plasma sheath.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of authors have used q-non-extensive velocity distribution to investigate the effects of non-thermal electrons on the plasma sheath dynamics. [21][22][23][24][25][26][27] For example, Driouch and Chatei investigated a magnetized dusty plasma sheath in the presence of a q-non-extensive distribution of electrons. [23] They assumed that the dust charge is constant.…”
Section: Introductionmentioning
confidence: 99%